Influencia de las deficientes relaciones intrafamiliares en la organizacion del comedor popular santa teresita del distrito de la esperanza en el año 2012 - Adrianzen Gutierrez, Rosita Mily (2013)
The domestic relations have been attracting interest from a few years ago, it exists within family systems a great deal of sensitivity that without proper management can generate major conflicts, family relationships can affect and change the future of a family, relationships between family and those against it, are directly related to the state of harmonious coexistence within the family system, the family relationship emerges as one of the cornerstones of the success of the family. Therefore, the following study was conducted at the Soup Kitchen "Santa Teresita" La Esperanza District, being the direct population of mothers who make up the dining room, with a total population of 35 mothers. This thesis work was carried out to analyze the influence of family relations in the organization of the Soup Kitchen "Santa Teresita" in 2012, in the district of La Esperanza, also the content of the thesis report is divided into the following chapters:  Chapter I: He mentions the problematic reality, history, theoretical, conceptual framework, the scientific problem, hypotheses and objectives.  Chapter II: This chapter lists the methods, techniques and tools to be applied to achieve the proposed objectives.  Chapter III: This refers to the presentation of results.  Chapter IV: the discussion and analysis thereof.  Chapter V: Disclosed conclusions and recommendations.  Chapter VI: Finally in this chapter presents the respective references and appendices.